Expression of monocyte chemoattractant protein 1 (MCP-1) in adult periodontal disease: increased monocyte chemotactic activity in crevicular fluids and induction of MCP-1 expression in gingival tissues. - Hanazawa, S (1993)
The present study shows that monocyte chemotactic activity in crevicular fluids increases with severity of the disease and that a monocyte chemoattractant, monocyte chemoattractant protein 1 (MCP-1), is expressed as the predominant cytokine of gingival tissues and their fibroblasts treated with Porphyromonas (Bacteroides) gingivalis lipopolysaccharide (P-LPS). High monocyte chemotactic activity in the crevicular fluids was neutralized significantly by antiserum specific for the JE/MCP-1 protein. Marked expression of the MCP-1 gene was observed in the gingival tissues of all adult periodontal patients tested, but not in those of healthy subjects. Monocyte chemotactic activity was observed in culture supernatants of human normal gingival tissues treated with P-LPS, and the chemotactic activity increased in a dose-related manner. Expression of MCP-1 in P-LPS-treated human gingival fibroblasts was further examined. P-LPS induced the MCP-1 gene expression in a dose- and treatment time-dependent manner. The MCP-1 gene product in the culture supernatant was detected as two forms with molecular masses of 11,000 and 15,000 Da by immunoprecipitation with the specific antiserum. The MCP-1 gene expression was induced in the fibroblasts treated with interleukin-1 beta and tumor necrosis factor alpha, but not with interleukin-6. These results suggest that gingival fibroblasts can participate in monocyte recruitment in gingival tissues of adult periodontal patients via the MCP-1 gene product and that MCP-1 plays an important role in the inflammatory reaction in the disease.